초전도 한류소자의 병렬연결에 따른 자속구속형 초전도 한류기의 특성 분석 - 吳金坤(Kum-Gon Oh); 鄭柄益(Byung-Ik Jung); 崔孝祥(Hyo-Sang Choi) (전기학회 논문지 P권, 57(2), 2008)
We investigated the operating characteristics of the flux-lock type superconducting fault current limiter(SFCL) with the parallel connection between the primary and secondary windings which are connected with two superconducting units in series. The parallel connection for current level increase of the flux-lock type SFCL is necessary to apply the SFCL into the power system. The resistance generated in superconducting units was dependent upon the winding direction of the primary and the secondary coils, which can reduce the power burden. The resistance of the superconducting elements in the subtractive polarity winding is higher than that of the additive polarity winding. The fault current limiting effect of the subtractive polarity winding is better than that of the additive polarity winding. From this results, we confirmed that the power capacity of the flux-lock type SFCL could be increased by the parallel connection of the superconducting units.